2015
DOI: 10.15632/jtam-pl.54.3.705
|View full text |Cite
|
Sign up to set email alerts
|

Combined load buckling for cylindrical shells based on a symplectic elasticity approach

Abstract: Buckling behavior of cylindrical shells subjected to combined pressure, torsion and axial compression is presented by employing a symplectic method. Both symmetric and non--symmetric boundary conditions are considered. Hamiltonian canonical equations are established by introducing four pairs of dual variables. Then, solution of fundamental equations is converted into a symplectic eigenvalue problem. It is concluded that the influence of pressure on buckling solutions is more significant than that due to compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Concerning the critical circumferential buckling stress of perfect cylindrical shells under uniform external pressure, the prEN 1993-1-6 (2021) [8] adopts several expressions as seen in Eqs. ( 4) to (6), which are for medium, short, and long cylinders, respectively.…”
Section: Circumferential Compressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the critical circumferential buckling stress of perfect cylindrical shells under uniform external pressure, the prEN 1993-1-6 (2021) [8] adopts several expressions as seen in Eqs. ( 4) to (6), which are for medium, short, and long cylinders, respectively.…”
Section: Circumferential Compressionmentioning
confidence: 99%
“…Real applications of thin-walled cylindrical shells showed that such structures are frequently subject to a combination of different types of loads, which are mainly axial compressive load, pressure, and torsional load rather than just one specific loading [6]. Understanding the buckling behavior of cylindrical shells under the combined action of two or all of these loads is thus particularly important (some research [7] has been done on this topic, and a lot of knowledge could be gained from it).…”
Section: Introductionmentioning
confidence: 99%